(untitled) (Research, Society and Development, 2021)
Evaluate the bacterial profile of samples of tracheal aspirates and urine cultures from patients admitted to the Intermediate Care Room of the University Hospital of Vale do São Francisco, Petrolina/PE. This is a descriptive, quantitative and retrospective study involving the analysis of the microbiological profile of samples collected from January to December 2020 by the Clinical Analysis Laboratory of the University Hospital. Data were tabulated in Excel® spreadsheets, where descriptive analysis was performed with absolute and percentage values. Bacterial identifications and antibiograms were performed using the BD Phoenix™ automated system, following the Clinical and Laboratory Standards Institute methodology. 120 tracheal aspirates were collected, being 55 positive (46%) for bacterial findings; the most prevalent pathogens were: Acinetobacter baumannii (40%), Klebsiella pneumoniae (16%) and Pseudomonas aeruginosa (11%). Regarding urine cultures, 183 were performed, 10 (5.46%) of which were positive for bacterial findings; the most prevalent bacteria were: Escherichia coli (40%) and Enterobacter cloacae (20%). A. baumannii showed 100% sensitivity to colistin and polymyxin B in tracheal aspirates, as well as K. pneumoniae to amikacin in all collected samples. E. coli showed some cephalospororin restriction, with the exception of cefoxitin, being sensitive; in addition, he had partial sensitivity to sulfamethoxazole+trimethoprim in the study. Knowledge of the microbiological profile of bacteria allows the development of preventive protocols and effective treatment, reducing mortality rates, length of stay and health care costs.